PENGARUH ABNORMAL AUDIT FEE, ADOPSI IFRS DAN KARAKTERISTIK PERUSAHAAN TERHADAP KUALITAS LABA - Rendi Octorio Siregar; Endang Kiswara (Diponegoro Journal of Accounting, 2018)
The purpose of this research is to analyze the association between abnormal audit fee, IFRS adoption, firm charactiristics and earnings quality proxied by discretionary accruals. Populations in this research are non financial companies listed in Indonesia Stock Exchange (IDX) in the period 2010-2016. The sample of this study consist of 184 companies listed in the Indonesia Stock Exchange. The data that was used in this research was secondary data. The samples of this research selected by using purposive sampling method. Model analysis using multiple linear regression analysis. This research revealed that abnormal audit fee, firm size, market-to-book and leverage ratio have negative and significant influence towards earnings quality. In the other hand, sales growth has positive and significant influence towards audit quality. While IFRS adoption, auditor firm size, and financial distress did not have significant influence towards earnings quality.